Bromination realities of 2,4-dihydroxyacetophenone and its derivatives - Похила, Б.; Горбуленко, Н.; Хиля, В. (Київський національний університет імені Тараса Шевченка, 2017)
Bromination process of resacetophenone was studied in a wide range of conditions – the heterogeneous bromination with CuBr2 and photochemical bromination with N-bromosuccinimide (NBS) in various solvents with an initiator and in the absence thereof. It is shown that under all these conditions, the bromination of resacetophenone passes not selectively, mainly in the nucleus, but not in the side chain, to form a mixture of different bromo derivatives, that have been identified by the aid of 1H NMR spectroscopy. Exactly the presence of two hydroxyl groups in the structure of the resacetophenone defines the direction of the bromination process. It is necessary to eliminate the influence of these groups for selective bromination of the resacetophenone side chain. The elimination of the influence of hydroxyl groups may be achieved by blockind them, for example, by their alkylation or benzylation. Examples of selective α-bromination of alkoxy and benzyloxy resacetophenone derivatives were described in the literature, but as it is known the subsequent process of removing the blocking and transition to the α-bromo-2,4-dihydroxyacetophenone often proves quite problematic. The bromination process of resacetophenone 2,4-diacetoxy and 2-hydroxy-4-acetoxy derivatives were explored. It was found that both the heterogeneous bromination with CuBr2 and the photochemical bromination with NBS in the ether of 2,4-diacetoxyacetophenone held in α-position to the carbonyl group with simultaneous deacylation to give α-bromo-2,4-dihydroxyacetophenone. but in the case of photochemical bromination desired α-bromo-2,4-dihydroxyacetophenone is formed in admixture with resacetophenone in a ratio of 1 to 3.The heterogeneous bromination with CuBr2 of 2-hydroxy-4-acetoxyacetophenone held in α-position to the carbonyl group with simultaneous deacylation to give α-bromo-2,4-dihydroxyacetophenone in admixture with resacetophenone in a ratio of 1 to 0,75.

Досліджено бромування резацетофенону в широкому спектрі умов – при гетерогенному бромуванні з СuBr2 та з N-бромсукцинімідом (NБС) в різних розчинниках з ініціатором та за його відсутності. Показано, що за означених умов, бромування резацетофенону проходить не селективно, головним чином у ядро, а не у бічний ланцюг, з утворенням суміші бромопохідних, які було ідентифіковано. Бромуванню резацетофенону у ядро безумовно сприяє наявність у його структурі двох гідроксильних груп. Селективне бромування бічного ланцюга відбувається за умови усунення впливу цих груп, що досягається їх блокуванням, наприклад, при алкілуванні ацилюванні, бензилюванні тощо. Досліджено бромування діацетоксипохідної резацетофенону. Показано, що бромування 2,4-діацетоксиацетофенону і при гетерогенному бромуванні з СuBr2 і при фотохімічному бромуванні з NБС в етері іде в α-положення до карбонільної групи з одночасним дезацилюванням, утворюючи α- бромо-2,4-дигідроксиацетофенон.
Реалії бромування 2,4-дигідроксиацетофенону та його похідних
Keywords: heterogeneous bromination CuBr2; photochemical bromination with N-bromosuccinimide; 5-bromo-2; 4-dihydroxyacetophenone; 3-bromo-2; 4-dihydroxyacetophenone; 5-dibromo-2; 4-dihydroxyacetophenone; α-bromo-2; 4-dihydroxyacetophenone; α-bromo-2; 4-dihydroxy-5-bromoacetophenone; -; гетерогенне бромування з СuBr2; фотохімічне бромування з N-бромсукцинімідом; 5-бромо-2; 4-дигідроксиацетофенон; 3-бромо-2; 4-дигідроксиацетофенон; 5-дибромо-2.4-дигідроксиацетофенон; α-бромо-2; 4-дигідроксиацетофенон; α-бромо-2; 4-дигідрокси-5-бромоацетофенон; -